Effectiveness Of Problem Solving Based Learning Model In The 21st Century In Improving Creativity and Science Learning Outcomes Of Grade IV Students - salwi, saiful; Wahid, Abdul; N, Jusmaniar (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine: (1) The application of the Problem Solving learning model based on 21st century learning in science learning for grade IV students of SD Negeri 1 Mbeleang. (2) How the Problem Solving learning model based on 21st century learning can improve the creativity and science learning outcomes of grade IV students of SD Negeri 1 Mbeleang. This study uses Classroom Action Research (CAR) with two cycles. Data collection techniques use learning outcome tests and observation sheets, analyzed quantitatively and qualitatively. The subjects of the study were 13 grade IV students, consisting of 5 boys and 8 girls. The results of the study showed an increase in the effectiveness of the Problem Solving learning model based on 21st century learning in improving creativity and learning outcomes with the average value of student learning outcomes increasing from 65.85% in cycle I to 79.69% in cycle II. Students' creativity also increased, with 2 students (15.38%) classified as very good, 8 students (61.54%) classified as good, and 3 students (23.07%) classified as sufficient in cycle II. The researcher concluded that the problem-solving model based on 21st century learning can improve creativity and learning outcomes of fourth grade students.